2023
DOI: 10.1063/5.0142014
|View full text |Cite
|
Sign up to set email alerts
|

Pair trajectories of uncharged conducting spheres in an electric field

Abstract: In this paper, we study the role of electrostatic forces on pair trajectories of two uncharged conducting spheres subject to an external electric field. We consider the hydrodynamic interactions between the spheres as they move relative to one another. Previous studies have shown that electric-field-induced forces on a two spheres system are always attractive, except for the configuration when the line joining the centers is perpendicular to the external electric field. In the current study, we derive the asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Experiments in a cloud chamber by Wang et al (2020) demonstrated that a strong electric field can dominate the collision process. Recently, Thiruvenkadam et al (2023) theoretically analysed the effects of an external electric on relative trajectories of a pair of uncharged conducting spheres, and they showed that electric-field-induced forces allow surface-to-surface contact in a finite time by overcoming continuum lubrication resistance. We plan to study the combined effects of gravity, non-continuum interactions, van der Waals forces and electric-field-induced forces on the collision dynamics of uncharged micron-sized droplets.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments in a cloud chamber by Wang et al (2020) demonstrated that a strong electric field can dominate the collision process. Recently, Thiruvenkadam et al (2023) theoretically analysed the effects of an external electric on relative trajectories of a pair of uncharged conducting spheres, and they showed that electric-field-induced forces allow surface-to-surface contact in a finite time by overcoming continuum lubrication resistance. We plan to study the combined effects of gravity, non-continuum interactions, van der Waals forces and electric-field-induced forces on the collision dynamics of uncharged micron-sized droplets.…”
Section: Discussionmentioning
confidence: 99%